Research data management: a bibliometric and altmetric study based on Dimensions - Gontijo, Marília Catarina Andrade; Hamanaka, Raíssa Yuri; de Araujo, Ronaldo Ferreira (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. This study aims to analyze the scientific production on research data management indexed in the Dimensions database. Design/Methodology/Approach. Using the term “research data management” in the Dimensions database, 677 articles were retrieved and analyzed employing bibliometric and altmetric indicators. The Altmetrics.com system was used to collect data from alternative virtual sources to measure the online attention received by the retrieved articles. Bibliometric networks from journals bibliographic coupling and keywords co-occurrence were generated using the VOSviewer software. Results/Discussion. Growth in scientific production over the period 1970-2021 was observed. The countries/regions with the highest rates of publications were the USA, Germany, and the United Kingdom. Among the most productive authors were Andrew Martin Cox, Stephen Pinfield, Marta Teperek, Mary Anne Kennan, and Amanda L. Whitmire. The most productive journals were the International Journal of Digital Curation, Journal of eScience Librarianship, and Data Science Journal, while the most representative research areas were Information and Computing Sciences, Information Systems, and Library and Information Studies. Conclusions. The multidisciplinarity in research data management was demonstrated by publications occurring in different fields of research, such as Information and Computing Sciences, Information Systems, Library and Information Studies, Medical and Health Sciences, and History and Archeology. About 60% of the publications had at least one citation, with a total of 3,598 citations found, featuring a growing academic impact. Originality/Value. This bibliometric and altmetric study allowed the analysis of the literature on research data management. The theme was investigated in the Dimensions database and analyzed using productivity, impact, and online attention indicators.